Structural characterization of the C-terminal domain of SARS-CoV-2 nucleocapsid protein - Renjie Zhou; Rui Zeng; Albrecht von Brunn; Jian Lei (Molecular Biomedicine, 2020)
Abstract The newly emerging severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in a global human health crisis. The CoV nucleocapsid (N) protein plays essential roles both in the viral genomic RNA packaging and the regulation of host cellular machinery. Here, to contribute to the structural information of the N protein, we describe the 2.0 Å crystal structure of the SARS-CoV-2 N protein C-terminal domain (N-CTD). The structure indicates an extensive interaction dimer in a domain-swapped manner. The interface of this dimer was first thoroughly illustrated. Also, the SARS-CoV-2 N-CTD dimerization form was verified in solution using size-exclusion chromatography. Based on the structural comparison of the N-CTDs from alpha-, beta-, and gamma-CoVs, we demonstrate the common and specific characteristics of the SARS-CoV-2 N-CTD. Furthermore, we provide evidence that the SARS-CoV-2 N-CTD possesses the binding ability to single-stranded RNA, single-stranded DNA as well as double-stranded DNA in vitro. In conclusion, this study could potentially accelerate research to understand the complete biological functions of the new CoV N protein.